Educational Disparity among Families living in Balochistan (Pakistan) on the Basis of Gender - Shabana Muhammad Anwar; Anam Aqil Khan; Qurratul Ain Sardar (Journal of Management Practices, Humanities and Social Sciences, 2022)
Education is the fundamental source that not only enhances knowledge but also builds the confidence of an individual. The development of any country utterly depends on its educational system, but unfortunately, the literacy ratio of education is low in Pakistan compared to other countries in Asia. The present study explores the educational disparity against girls based on gender in Pakistan. Geographically Balochistan is the largest province of Pakistan and is instilled with the tribal system. The people of Balochistan strongly follow their cultural values strictly, where the male members of the society are only considered the head of their families. In patriarchal societies, males are authoritative and have the power of decisions over their women. In Balochistan and Khyber Pakhtoon Khaw, females are restricted merely to staying inside the house and strictly prohibited from taking their life’s decisions. Furthermore, the women are deprived of their rights. Education is the source of self-development and helps to progress in the country. The focus of this study is to highlight the educational discrimination against girls. The nature of the study is quantitative, and the respondents were selected from (Arts faculty) of all the degree colleges of Quetta city (capital of Baluchistan) through probability simple random sampling. The sample size was approximately 200 students from all degree colleges. Data were analyzed by the SPSS (Statistical package for social sciences). The p-value of .003 shows the relationship between gender discrimination and educational opportunities. Finally, the results demonstrated that families are not serious and are not paying any concentration on girls’ education. Girls do not have facilities at the family level, and the access to education for girls is not easy due to males’ superiority.